Automated Synthesis of 18F-BCPP-EF {2-tert-Butyl-4-Chloro-5-{6-[2-(2[18F]fluoroethoxy)-Ethoxy]-Pyridin-3-ylmethoxy}-2H-Pyridazin-3-One for Imaging of Mitochondrial Complex 1 in Parkinson’s Disease - Kaur, Tanpreet; Brooks, Allen F.; Liddell, Katherine M.; Henderson, Bradford D.; Hockley, Brian G.; Bohnen, Nicolaas I.; Albin, Roger L.; Scott, Peter J. H. (Frontiers in Chemistry, 2022)
Graphical Abstract